Integration of Prasiaga Values in The Independent Curriculum to Foster Early Childhood Independence - Arzaqi, Roby Naufal; Rahayu, Aisah Karunia; Hendriawan, Deri (PIAUD Universitas Islam Negeri Sunan Kudus, 2025)
This study examines the integration of Prasiaga values within the Independent Curriculum and their contribution to the development of early childhood independence. Employing a qualitative case study design, the research involved two A-accredited early childhood education (ECE) institutions that had implemented Prasiaga-based activities. Data were collected through in-depth interviews, participatory observations, and document analysis, and were analyzed using thematic analysis supported by source triangulation. The findings reveal that the two institutions integrate Prasiaga values through different approaches. The first ECE implements a creative model based on digital exploration, while the second adopts a structured habituation approach. Both approaches contribute to children’s independence, particularly in initiative, responsibility, decision-making, and readiness to engage in daily tasks. Nevertheless, challenges arise from variations in children’s abilities and teachers’ limitations in designing value-based activities. These findings contribute theoretically to the discourse on character education within the Independent Curriculum and offer practical implications for PAUD institutions in strengthening the systematic integration of Prasiaga values.